Assessing user preferences for sexually transmitted infection testing services: a discrete choice experiment. Issue 7 (1st June 2012) - Miners, Alec; Llewellyn, Carrie; Pollard, Alex; Lagarde, Mylene; Richardson, Daniel; Cairns, John; Fisher, Martin; Smith, Helen
Abstract : Objective: To assess user preferences for different aspects of sexually transmitted infection (STI) testing services. Design: A discrete choice experiment. Setting: 14 centres offering tests for STIs in East Sussex, England. Participants: People testing for STIs. Main outcome measure: (Adjusted) ORs in relation to preferred service characteristics. Results: 3358 questionnaires were returned; mean age 26 (SD 9.4) years. 70% (2366) were recruited from genitourinary medicine (GUM) clinics. The analysis suggested that the most important characteristics to users were whether 'staff had specialist STI knowledge' compared with 'staff without it' (OR 2.55; 95% CI 2.47 to 2.63) and whether 'tests for all STIs' were offered rather than 'some' (OR 2.19; 95% CI 2.12 to 2.25). They remained the most important two service characteristics despite stratifying the analysis by variables such as age and sex. Staff levels of expertise were viewed as particularly important by people attending CASH centres, women and non-men who have sex with men. A 'text or call to a mobile phone' and 'dropping in and waiting' were generally the preferred methods of results reporting and appointment system, respectively. Conclusions: This study suggests that people testing for STIs place particular importance on testing for all infections rather than some and staff with specialist STI knowledge. Thus, targets based purely on waiting up to 48 h for an appointment are misguided from a user perspective.